ETHNICAL STATE AND ETHNICAL BEHAVIOR OF THE DAGESTAN RUSSIANS - Sahbanova, M M; Lysenko, U M; Mamaraev, R M (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with ethnic health of the Russian-speaking population of the Dagestan Republic. The authors analyze the causes of their migration from the republic, define the assessment of the interethnic situation in the place of their residence that existsin the mass consciousness ofthe Russians of Dagestan, and characterize peculiarities of their ethnic behavior and their commitment tomaintain social contacts with other ethnic communities.
Keywords: Russians of Dagestan; Dagestan peoples; interethnic relations; migration; Russian-speaking population; ethnic identity; ethnic behavior